2015
DOI: 10.1093/mutage/geu051
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory erythropoiesis has no impact on the outcome of the in vivo Pig-a mutation assay in rats following treatment with the haemolytic agent 2-butoxyethanol

Abstract: The Pig-a assay has rapidly gained international interest as a useful tool for assessing the mutagenic potential of compounds in vivo. Although a large number of compounds, including both mutagens and non-mutagens, have been tested in the rat Pig-a assay in haematopoietic cells, there is limited understanding of how perturbations in haematopoiesis affect assay performance. Of particular concern is the possibility that regenerative haematopoiesis alone, without exposure to a genotoxic agent, could result in ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
3
7
0
2
Order By: Relevance
“…Our data show that despite significant perturbations in hematopoietic homeostasis, increases in the number of RBC CD59− or RET CD59− were not seen 5, 18, or 49 days after confirming regenerative anemia in the bleed group animals. These findings are consistent with those reported by Kenyon et al, where the nongenotoxic, hemolytic compound 2‐butoxyethanol administered as a single dose or over 28 days up to 450 mg kg −1 day −1 led to marked hematopoietic responses, but no increases in mutant RETs or RBCs during and up to 57 days after the initiation of treatment [Kenyon et al, ]. This current work further confirms that regenerative responses to conditions producing anemia in rats would not lead to an increase in cells with Pig‐a mutations in the absence of a mutagenic agent, and provides further evidence of the robustness of the Pig‐a Assay as a tool for the in vivo assessment of potentially mutagenic compounds.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data show that despite significant perturbations in hematopoietic homeostasis, increases in the number of RBC CD59− or RET CD59− were not seen 5, 18, or 49 days after confirming regenerative anemia in the bleed group animals. These findings are consistent with those reported by Kenyon et al, where the nongenotoxic, hemolytic compound 2‐butoxyethanol administered as a single dose or over 28 days up to 450 mg kg −1 day −1 led to marked hematopoietic responses, but no increases in mutant RETs or RBCs during and up to 57 days after the initiation of treatment [Kenyon et al, ]. This current work further confirms that regenerative responses to conditions producing anemia in rats would not lead to an increase in cells with Pig‐a mutations in the absence of a mutagenic agent, and provides further evidence of the robustness of the Pig‐a Assay as a tool for the in vivo assessment of potentially mutagenic compounds.…”
Section: Discussionsupporting
confidence: 93%
“…Additional research is needed to understand all of the factors that can influence the number of mutant cells observed in experimental animals [Kenyon et al, ; Labash et al, ; Wickliffe et al, ]. This knowledge is important, because it is not currently known if the clonal expansion of single mutant progenitor cells can influence the ability to detect a signal after exposure to a mutagen [Heddle, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflammation and increase in cell division associated with IBD might be responsible for the slight elevation in PIG‐A MF. But some rodent Pig‐a studies also indicated that the regenerative erythropoietic response does not lead to increase Pig‐a MFs (Kenyon et al ; Nicolette et al ). Thus, we interpret the results of PIG‐A assay in our study only as a weak positive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Le séquençage du gène PIG-A réalisé sur des cellules issues de patients HPN et de sujets sains a ainsi identifié plus de 100 mutations inactivantes (parmi lesquelles des mutations non-sens, faux-sens, des décalages du cadre de lecture, des substitutions, et de larges délétions) aboutissant toutes au même phénotype de déficience en GPI, suggérant que le gène PIG-A puisse être sensible à un grand nombre de modes d'actions génotoxiques [15,34]. Deux lacunes identifiées par l'IWGT en 2015 ont été comblées par la publication de deux études récentes : les performances du test ne dépendent en fait pas du nombre de copies du chromosome X portées par l'individu, les fréquences spontanées et induites de cellules mutées pour le gène PIG-A n'étant pas différentes entre mâles et femelles [23,35,36] ; l'érythropoïèse compensatoire observée après exposition à un agent hémolysant non génotoxique (comme le 2-butoxyéthanol) n'entraîne pas d'augmentation de la fréquence des cellules GPI-déficientes [37]. Ces qualités ont initié l'évaluation du test PIG-A in vitro : le séquen-çage du gène PIG-A réalisé sur des lymphoblastes humains cultivés in vitro et soumis à divers génotoxiques connus, a révélé des résultats comparables à ceux obtenus in vivo chez la souris après exposition aux mêmes agents [38].…”
Section: Cytométrie De Fluxunclassified